2021
DOI: 10.1111/iwj.13585
|View full text |Cite
|
Sign up to set email alerts
|

Modified compression therapy in mixed arterial–venous leg ulcers: An integrative review

Abstract: Leg ulcers remain an increased burden to healthcare cost and morbidity in modern society. While most leg ulcers are venous in origin, recognition and prompt identification of concomitant arterial occlusive disease is critical to determine underlying aetiology and subsequent management. This integrative review presents the current evidence to establish the role of modified compression therapy (MCT) in treatment of mixed arterial venous leg ulcers (MAVLU). A literature search was conducted using the electronic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…We found one review investigating treatment for the mixed ulcers and arterial ulcers (MAVLU), i.e. VLUs with coexisting PAD, and presented the effect of the MCT with or without revascularisation depending on patients ABI (85). Lim and colleagues showed that MCT with a pressure between 20 and 30mmHg can promote healing in mixed ulcers when moderate arterial insufficiency is present (0.5 ≤ ABI ≤0.8), but if ABI is <0.5 (arterial ulcers), MCT can only be considered when acceptable ABI is achieved (87).…”
Section: Compression For Mixed Ulcersmentioning
confidence: 99%
“…We found one review investigating treatment for the mixed ulcers and arterial ulcers (MAVLU), i.e. VLUs with coexisting PAD, and presented the effect of the MCT with or without revascularisation depending on patients ABI (85). Lim and colleagues showed that MCT with a pressure between 20 and 30mmHg can promote healing in mixed ulcers when moderate arterial insufficiency is present (0.5 ≤ ABI ≤0.8), but if ABI is <0.5 (arterial ulcers), MCT can only be considered when acceptable ABI is achieved (87).…”
Section: Compression For Mixed Ulcersmentioning
confidence: 99%
“…Since this review was undertaken in May 2019, the National Wound Care Strategy Programme (NWCSP) has developed evidence-informed recommendation and outlines pathways to support development of local protocols in preventing, assessing, and treating patients with leg ulcers. 40 The body recognises the importance of optimising the correct use of healthcare resources while improving healing, and signpost clinicians to relevant clinical guidelines or evidence, with the aim of ultimately providing a national equitable, accessible, and standardised care.…”
Section: Healing Times With Revascularisation Prior To Mct In Mavlumentioning
confidence: 99%
“… 3 Peripheral vascular pathology entails high costs and a decrease in patients' quality of life. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 The application of compression bandage has been considered a contraindication in the presence of arteriopathy due to the possible association of an ischemic effect induced by the bandage. 5 , 9 , 10 In arteriovenous ulcers, the lack of application of this treatment means that the venous part of the disease is ignored, delaying the healing process of the ulcer. 11 The existing evidence on this treatment for those ulcers is still insufficient or low and there is little agreement on the pressure used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation